Axel Motors - Sharma, Meenakshi, active 2019; Sharma, Ruchir (London : Indian Institute of Management, Ahmedabad, 2019)
The case concerns Anil Mishra, Head of Sales at the corporate office of Axel Motors India in Gurgaon. The team has received an email from Maximilian Klotz, the Head of Strategy at the Axel Motors' Headquarters (HQ) in Regensburg, Germany. Klotz has expressed displeasure at the fall in sales and complete dissatisfaction with the performance of Axel Motors India. Further, Klotz's email has attributed the dismal performance to the introduction of a compact sedan on the recommendations of the Axel India office. The introduction of this sedan had, in fact, been approved by HQ on the recommendation of the Axel Motors India team after a very protracted process. Now Klotz blamed it for damaging the sales as well as the reputation of the company. He warned that unless these trends were swiftly addressed and rectified, the company would exit the sub-4-metre sedan segment.
Originally Published InSharma, M., & Sharma, R. (2019). Axel Motors. IIMA/COMM0024. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business communication -- Case studies; Conflict management -- Case studies